A preliminary study on pre-treatment solutions towards chili seeds germination / Siti Nur Azmu’i Abdullah, Noor Amira Muhammad and Saiyidah Nafisah Hashim - Abdullah, Siti Nur Azmu’i; Muhammad, Noor Amira; Hashim, Saiyidah Nafisah (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Capsicum annuum L. is an important crop due to its large scale consumption in many countries. However, low germination process of chili seed is the common problem encountered by planters. Seed priming is believed able to overcome this problem by stimulate imbibition of seed using pre- treatment solution. In this study effect of two pre-treatment solutions; gibberellic acid (GA 3 ) and hydrogen peroxide (H 2 O 2 ) on germination process of chili seeds were evaluated. Experimental works were carried out through imbibition of chili seeds in the different concentrations of pre- treatment solution and imbibition period (one hour and 24 hours). After imbibition procedure, chili seeds were air dried for one hour before sowing process. Germination percentage and growing performance of chili seeds were assessed after seven days of sowing. The germination percentage of chili seed were identified based on percentage of successfully germinated chili seed while the growing performances were assessed through the average length of root, stem and leaf. Study has found that the most suitable pre-treatment solution for chili seeds is 6% of GA 3 with one hour imbibition period with highest germination percentage (92%) and average length of root, stem and leaf of 3.2±0.1 cm, 3.1±0.1 cm and 1.0±0.2 cm respectively. GA 3 significantly speed up germination process by regulating protein synthesis, hence suitable to be used as pre-treatment solution.